Inference of the phenotypic resistance profile of Pseudomonas aeruginosa through an interpretative reading of the antibiogram in a pediatric hospital. 2006-2014. (2016)
Introduction: Pseudomonas aeruginosa behaves as an opportunistic pathogen involved in hospital infections, with high capacity to generate resistance to antibiotic treatment. The interpretative reading of the antibiogram makes possible inferring these resistance mechanisms and establishing appropriate antibiotic treatment.Objective: The interpretative reading of the antibiogram seeks to infer the resistance phenotype of P. aeruginosa at Fundación Hospital de la Misericordia (HOMI, by its acronym in Spanish) between 2006 and 2014.Materials and methods: Descriptive cross-sectional study where a search of positive antibiogram reports for P. aeruginosa was performed. The resistance phenotype was deduced based on the interpretative reading of the antibiogram.Results: A sample of 463 positive antibiograms for P. aeruginosa was obtained; these samples were taken from children aged 0 to 17, showing a higher prevalence among infants and toddlers. The antibiograms mainly came from male subjects (62.2%). The most frequent hospitalization services were: PICU —pediatric intensive care unit— (30.2%) and general hospitalization (27.3%). The most common sources of isolation were: blood (24.4%) and urine (23.8%). 11 phenotypes were characterized, being the most common: natural phenotype (63.2%), loss of porin OprD (5.7%) and partial and full AmpC derepression (8.4% and 8.2%, respectively).Conclusion: Isolation of P. aeruginosa at HOMI predominantly shows a natural phenotype. The interpretative reading of the antibiogram allowed inferring 11 phenotypes.